Implementasi Prinsip Hukum Ekonomi Syari’ah dalam Produk Pembiayaan Bank Syari’ah Indonesia (BSI) - Mohamad Khandik; Muhammad Royani; Ahmad Abroza; Arsyad Ali Fami (Jurnal Multidisiplin Indonesia, 2026)
This study analyzes the implementation of sharia economic principles in Bank Syariah Indonesia (BSI) financing products after the 2021 merger, focusing on murabahah, mudharabah, musyarakah mutanaqisah, and ijarah contracts. Using a descriptive qualitative approach through literature review of BSI annual reports, DSN-MUI fatwas, OJK regulations, and scientific journals, the study found a sharia compliance rate of 92-95% with a low NPF of 2.5%, supported by DPS supervision and contract digitization. The results indicate that the dominance of murabahah (60%) effectively avoids riba and gharar, although challenges with customer literacy and flat yields are minor deviations. The discussion confirms the link between sharia theory and BSI practices, supporting 25% year-on-year asset growth and a 15% market share target by 2027. Improved AI monitoring for mudharabah and new fintech fatwas are recommended to strengthen financial inclusion. Therefore, this study recommends increasing the use of Artificial Intelligence (AI) technology in monitoring profit-sharing financing, such as mudharabah, and improving public education and Sharia financial literacy. Thus, the implementation of Sharia economic legal principles at BSI is expected to be more optimal, adaptive, and sustainable in supporting the Sharia financial system in Indonesia.